¿Cómo aproximarnos al diagnóstico psicológico de los problemas específicos de aprendizaje? - Thorne, Cecilia (1985)
A dynamic approach in the diagnosis of learning disabilities (L.D.) is presented. The main goal is to describe in detail the findings of the assesment process, that will permit the planning of a remediation program whose objective is to assist the learning disabled child. The factors that are taken into consideration are: intellectual, specific abílities, school achieved and personality.